2010
DOI: 10.1038/jcbfm.2010.118
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Genetic and Renovascular Chronic Arterial Hypertension on the Acute Spatiotemporal Evolution of the Ischemic Penumbra: A Sequential Study with MRI in the Rat

Abstract: Although chronic arterial hypertension (CAH) increases the risk of stroke and the severity of the resultant lesion, it is rarely integrated in preclinical studies. Here, we analyzed the impact of CAH on the acute spatiotemporal evolution of the ischemic penumbra as defined by the perfusion-weighted imaging/diffusion-weighted imaging mismatch. Sequential 7T-MRI examinations were performed from 30 minutes up to 4 hours after permanent cerebral ischemia in genetically hypertensive rats (spontaneously hypertensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 29 publications
(40 reference statements)
2
38
0
2
Order By: Relevance
“…The phenomenon of negative mismatch has been identified previously in rodent stroke models (Foley et al, 2010;Letourneur et al, 2011) and may potentially occur as a consequence of peri-infarct spreading depolarizations from the ischemic core, increasing cellular injury in adjacent oligemic tissue, and extending the outer boundary of injured tissue beyond the perfusion deficit. High levels of potassium ions and glutamate in the ischemic core can actively induce tissue depolarization, ionic imbalances and glutamate spread into adjacent tissue and peri-infarct depolarizations can originate in the striatum in rats (Hartings et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The phenomenon of negative mismatch has been identified previously in rodent stroke models (Foley et al, 2010;Letourneur et al, 2011) and may potentially occur as a consequence of peri-infarct spreading depolarizations from the ischemic core, increasing cellular injury in adjacent oligemic tissue, and extending the outer boundary of injured tissue beyond the perfusion deficit. High levels of potassium ions and glutamate in the ischemic core can actively induce tissue depolarization, ionic imbalances and glutamate spread into adjacent tissue and peri-infarct depolarizations can originate in the striatum in rats (Hartings et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, our data may have failed to recognize potential strain differences in penumbra volume since we could not examine the full extent of the rostral and caudal poles of the penumbra due to the time constraints associated with CBF data acquisition. Letourneur et al (2011) showed a reduced mismatch volume in SHR and renovascular hypertensive (RH) WKY rats compared with normotensive WKY rats from 30 minutes to 4 hours after MCAO. Our data show that penumbra volume was not significantly different between WKY and SHRSP from 1 to 4 hours using volumetric mismatch, spatial mismatch, or ADC lesion growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All animal experiments were carried out under the previous European directive (86/609/EEC) as enacted in the national legislation. Individual licenses to investigate SR (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26), MB (14-71), JT , EP (14-79), OT (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) and SV are held and the study was approved by the regional ethical committee for animal research and health-care 'Comité Régional d'Éthique en matière d'Expérimentation Animale pour la Normandie' (CEEAN, agreement no. 0507-02).…”
Section: Methods Animalsmentioning
confidence: 99%
“…There are large differences in the volume of penumbral tissue and the rate it is incorporated into the infarct core following occlusion of the MCA in different rat strains. [23][24][25][26] This is generally thought to be due to differences in the residual blood flow to the ischemic brain via the leptomeningeal collateral circulation. 27 We have previously demonstrated that inadvertent occlusion of the AChA, an important internal collateral supply to the MCA results in larger 24-h histological infarct volumes.…”
Section: Discussionmentioning
confidence: 99%